A neurobiological mechanism linking transportation noise to cardiovascular disease in humans. (26th November 2019) - Osborne, Michael T; Radfar, Azar; Hassan, Malek Z O; Abohashem, Shady; Oberfeld, Blake; Patrich, Tomas; Tung, Brian; Wang, Ying; Ishai, Amorina; Scott, James A; Shin, Lisa M; Fayad, Zahi A; et al.
Abstract: Aims: Chronic noise exposure associates with increased cardiovascular disease (CVD) risk; however, the role of confounders and the underlying mechanism remain incompletely defined. The amygdala, a limbic centre involved in stress perception, participates in the response to noise. Higher amygdalar metabolic activity (AmygA) associates with increased CVD risk through a mechanism involving heightened arterial inflammation (ArtI). Accordingly, in this retrospective study, we tested whether greater noise exposure associates with higher: (i) AmygA, (ii) ArtI, and (iii) risk for major adverse cardiovascular disease events (MACE). Methods and results: Adults ( N  = 498) without CVD or active cancer underwent clinical 18 F-fluorodeoxyglucose positron emission tomography/computed tomography imaging. Amygdalar metabolic activity and ArtI were measured, and MACE within 5 years was adjudicated. Average 24-h transportation noise and potential confounders were estimated at each individual's home address. Over a median 4.06 years, 40 individuals experienced MACE. Higher noise exposure (per 5 dBA increase) predicted MACE [hazard ratio (95% confidence interval, CI) 1.341 (1.147–1.567), P  < 0.001] and remained robust to multivariable adjustments. Higher noise exposure associated with increased AmygA [standardized β (95% CI) 0.112 (0.051–0.174), P  < 0.001] and ArtI [0.045 (0.001–0.090), P  = 0.047]. Mediation analysis suggested that higher noise exposure associates with MACE via a serial mechanism involving heightened AmygA and ArtI that accounts for 12–26% of this relationship. Conclusion: Our findings suggest that noise exposure associates with MACE via a mechanism that begins with increased stress-associated limbic (amygdalar) activity and includes heightened arterial inflammation. This potential neurobiological mechanism linking noise to CVD merits further evaluation in a prospective population.